Effects of lipid emulsions on unbound bilirubin and response to phototherapy in preterm infants. (30th December 2022) - Sasenick, Jonathan; Kleinfeld, Alan; Huber, Andrew; Oh, William; Hegyi, Thomas; Weinberger, Barry
Abstract: Objective: Bilirubin-induced neurotoxicity is mediated by the fraction of total serum bilirubin (TSB) not bound to albumin (Bf). Unbound free fatty acids (FFAu) generated from lipid emulsions compete with bilirubin for albumin binding, increasing Bf. Soy-based (IL) and soy-MCT-olive-fish oil-based (SMOF) lipid emulsions contain different fatty acids with distinct albumin binding affinities. IL increases Bf in preterm infants, but the effects of SMOF on Bf are not known. Our objective was to compare changes in TSB, Bf, FFAu, and response to phototherapy in preterm infants receiving SMOF and IL. We hypothesized that SMOF would be associated with lower Bf and better response to phototherapy than IL. Methods: Very preterm and low birth weight infants (<1500 g, <32 weeks) were infused with IL ( n  = 20) or SMOF ( n  = 20) as prescribed by providers. Phototherapy was prescribed using the standard care practice. FFAu profiles and levels, TSB, and Bf were measured on 0, 1, 2, and 3 g/kg/day of lipid infusion and at the initiation and termination of phototherapy. TSB was analyzed in the clinical laboratory using the diazo technique. FFAu and Bf were measured using fluorescent probes. Results: Escalating doses of IL and SMOF increased FFAu levels and Bf, but not TSB. Phototherapy did not significantly decrease Bf for infants receiving either lipid. IL-treated infants had higher levels of unbound linoleic acid, and SMOF-treated infants had higher unbound arachidonic, oleic, and docosahexaenoic acids. Conclusions: IL and SMOF both increase Bf similarly, and phototherapy does not significantly affect Bf for infants receiving them.